2010
DOI: 10.1097/pai.0b013e3181bcb2da
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of P73 Overexpression in Colorectal Carcinoma

Abstract: All these findings prove that p73 expression should be considered as a valuable poor prognostic marker. Our data also suggest that TP73 gene may play a role in colorectal carcinoma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…ΔNp73 has also been detected in EVs from CRC patients and associated with a worse outcome [ 18 ]. Interestingly, although TAp73 presents tumor suppressor abilities similar to those described for TP53 , it has been described as overexpressed in many human tumors including CRC and associated with poorer survival [ 15 , 41 , 42 , 43 , 44 ]. Remarkably, its status in EVs from cancer patients has not been tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…ΔNp73 has also been detected in EVs from CRC patients and associated with a worse outcome [ 18 ]. Interestingly, although TAp73 presents tumor suppressor abilities similar to those described for TP53 , it has been described as overexpressed in many human tumors including CRC and associated with poorer survival [ 15 , 41 , 42 , 43 , 44 ]. Remarkably, its status in EVs from cancer patients has not been tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that positive immunohistochemical staining TP73 was associated with worse clinical outcome in extrahepatic bile duct carcinoma [19], cholangiocellular carcinoma [20], hepatocellular carcinoma [39,43], colorectal cancer [26,44], ovarian cancer [28] and esophageal squamous cell carcinoma [36]. However, we further evaluated the association between TP73 expression and overall survival of cervical cancer patients in TCGA database, and found that TP73 expression was positively correlated with overall survival time in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the ten transcription regulators, we noted that the overexpression of EPAS1 was associated with poor prognosis in colorectal carcinoma, according to previous reports [ 19 21 ]. Polymorphism and expression of TP73 were associated with carcinogenesis and colorectal carcinoma development [ 22 , 23 ]. TEAD1 was reported to enhance the proliferation in colorectal carcinoma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%